Buckling-driven periodic wrinkle patterns in a film-lattice structure. (July 2020) - Zeng, Guangzhi; Zhao, Tianyu; Chen, Jianlong; Yan, Dong; Zhang, Kai
Abstract: Film structures have been widely used in flexible electronics, material science, metrology, biomedical engineering and aerospace engineering. When a thin film is loaded with compressive stresses, buckling accompanied by wrinkles is likely to occur under constrained boundaries. Many previous studies have focused on the wrinkling mechanism of a free-standing film or a film–substrate structure, in which compressive stresses in the film are caused by the mismatch between the film and the imposed constrains from its boundaries or the substrate. Instead of using the homogeneous substrate, here we propose a film-lattice structure consisting of a thin film bonded to a bottom-supported lattice. By controlling the buckling of the lattice structure, a distribution of compressive loads can be applied to the film, finally resulting in the generation of periodic wrinkles. Physical mechanism on the buckling-driven wrinkle pattern is investigated with the increasing loading. Dimensionless parameters and their effect on governing the wrinkling mode are also analyzed numerically. The exploration on features of the wrinkles on the film shows that the wrinkle pattern can be controlled by designing the lattice substrate. Our works could help understand the wrinkling caused by the buckling of a complex substrate and guide the harnessing of wrinkles in the design of new materials and structures.